Contribution to a revision of the genus Pratylenchoides Winslow, 1958 (Nematoda: Merliniidae), with redescription of P. erzurumensis Yüksel, 1977 from Iran - Ghaderi, Reza; Karegar, Akbar (Zootaxa, 2014)
Morphological and morphometric studies were conducted on the populations and paratypes of 14 species of the genus Pratylenchoides, including P. alkani, P. acuticauda, P. arenarius, P. arenicola, P. bacilisemenus, P. crenicauda, P. erzurumensis, P. heathi, P. laticauda, P. ritteri, P. rivalis, P. sheri, P. utahensis and P. variabilis. In addition, P. erzurumensis was redescribed based on a bisexual population from western Iran. The conoid head of males is an additional diagnostic character of this species distinguishing it from the closely related P. laticauda and P. camachoi. Based on detailed study of the main characters, synonymies of P. arenarius with P. bacilisemenus and P. variabilis with P. crenicauda are proposed. Synonymy of P. alkani with P. ritteri is supported also by morphological and biological evidence. Some taxonomic notes are made on some other species of the genus. Finally, a diagnostic compendium and key is provided for species identification.